DIRECTIONS FOR IMPROVING THE AUDIT OF OBLIGATIONS IN THE FIELD OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Amirov Asqar Aktamovich (Researchparks Publishing, 2023)
This article highlights the differences and features of accounting for liabilities according to National accounting standard (NAS) and National accounting standard (NAS) in the context of the transition to the digital economy . Also from BHMS account of liabilities The problematic aspects that arise in the process of transformation of National accounting standard (NAS) are highlighted and proposals are given..